Evaluación Inclusiva e Intercultural: una mirada a la educación en el pueblo Waorani - Yépez Rosero, Alexandra (2018)
The following investigation gives a bird's eye view of social Inclusion and Interculturality in the area of General Basic Education in Ecuador. This article reflects upon the reality that the Community Center for Intercultural and Bilingual Education ,located in the Yasuní National Park, undergoes by reviewing important documents that contain policies and regulations which reveal the fragmented know-how about social inclusion and interculturality. The center attends to Waorani schoolchildren. What intends to be clarified is if the aplication of instruments intended to measure knowledge ,skills and competences, necessary for better school performance, need to be contextualized and take into consideration sociocultural diversity and the principle of interculturality proposed in the Ecuadorian Constitution of 2008. The results of the application of a battery of standarized CUMANIN y AE-P tests were observed ,which although are highly reliable, do not take into consideration social cultural contexts. Such results do not convey the skills and competencies that Waorani children have thus, the need for tests to be previously adapted to social cultural contexts in order to abide by the principles of social inclusion, interculturality and diversity.